Regional and global spillovers and diversification opportunities in the GCC equity sectors - Balcilar, Mehmet; Demirer, Riza; Hammoudeh, Shawkat (Elsevier, 2015)
This paper examines the international diversification benefits of bloc-wide equity sectors in the oil-rich Gulf Cooperation Council (GCC) countries by comparing alternative spillover models that encompass local, regional and global factors. Some GCC-wide equity sectors/subsectors are found to display segmentation from global markets during periods of high and extreme market volatility, and thus can serve as safe havens for international portfolio investors during such periods. The in- and out-of-sample portfolio analyses further suggest that supplementing global portfolios with positions in the GCC markets yields significant international diversification benefits, consistently offering much improved risk-adjusted returns across the alternative spillover models. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: GCC-wide equity sectors; Multivariate regime-switching; Time-varying correlations; Financial integration; International portfolio diversification